Associação entre transtornos mentais e tentativa de suicídio - Fortuna, Cassia Tasca (2020)
Objective: To analyze the association between the prevalence of suicide attempts and patients diagnosed with mental disorders followed up at a Psychosocial Care Center located in the south of Santa Catarina. Methods: The methodology used was a cross-sectional study. The research sites were the Psychosocial Care Center and the Center for the Prevention of Violence and Health Promotion. In these locations, electronic medical records of patients undergoing treatment during the study period and the individual notification forms for Interpersonal/Self-harassed violence filed in the System were analyzed Information System for Notifiable Diseases. Results: among 341 patients undergoing treatment at the CAPS, 19.6% had attempted suicide, among them, 62.2% were female, with a partner, aged between 18 and 24 years; 40.3% of patients reported mental disorder as a reason for this act and 71% had been executed through poisoning. Discussion: Patients diagnosed with personality or mood disorders were associated with attempted suicide, with significant relative risk when compared to other disorders, corroborating national and international literature. Conclusions: Some types of specific mental disorders offer a higher risk of attempting suicide, highlighting the need for trained professionals to carry out diagnosis and appropriate treatments, and campaigns to value life, in order to reduce the prevalence of suicide attempts.